Perilaku Kriminalitas Perempuan: Studi Kasus Narapidana Perempuan di Lembaga Pemasyarakatan Wanita Kelas II A Sungguminasa Gowa: Perilaku Kriminalitas Perempuan: Studi Kasus Narapidana Perempuan di Lembaga Pemasyarakatan Wanita Kelas II A Sungguminasa Gowa - Jusnawati; Sunaniah (Jurnal Sosiologi Nusantara, 2024)
Increasing women's participation in the public sphere and the roles that women play show increased welfare for women. This is the impact of awareness about gender equality in various fields. However, this expanded role also extends to the realm of criminal activity. Although men still dominate crime perpetrators, there has been a significant increase in crimes committed by women. Therefore, this research aims to explain the factors that cause women to commit crimes and the impact of the training they receive. The research method used is qualitative with observational data collection techniques without participation, in-depth interviews with 20 women convicts, documentation, and audio and visual material. Data analysis was carried out in three stages: data reduction, presentation, and conclusion. The research results show why women commit crimes: 1) Social factors are related to the social environment and destructive relationships in society, and 2) Educational factors, namely the lack of knowledge of better alternative actions and risk considerations. 3) Economic factors, namely demands for the cost of living. 4) Patriarchal cultural factors that trigger women's psychological pressure. The impact of the training obtained is the formation of a new awareness of sound life principles, skills and abilities training, social empowerment, and economic independence.